CERAM : AN INVESTIGATION OF RESPONSE TO THE CHANGING CLIMATE IN GREATER JAKARTA - Syarifah Aini Dalimunthe; Intan Adhi Perdana Putri (Jurnal Sosioteknologi, 2016)
Over the past decade, increased knowledge coupled with economic incentives, subsidies and relatedinterventions has raised awareness and concern about climate change in vulnerable Greater Jakarta. Thispaper will analyze index and status of responsiveness and pro environmental behavior of each region withinGreater Jakarta towards climate change by means of Climate Change Eï¬€ectiveness Response Assessment(CERAM) using multidimensional scaling technique (MDS). Total data used is 1261 respondents. Overall,the index has shown Bogor responded and acted the most to climate change and likely has had more proenvironmental behavior. Bekasi, meanwhile, holds the highest index in individual resources (71.47). Themost inï¬‚uencing attribute regarding the index and status response are willingness to take out insurance. Theresult of this study will provide evidence to support more ambitious regional response to climate changebased on the status of responsiveness of each region in Greater Jakarta.